Risk factors for advanced fibrosis in metabolic dysfunction-associated steatotic liver disease in patients with diabetes mellitus type 2 - Miranda Manrique, Gonzalo (2023)
Objectives: To determine sociodemographic, anthropometric, biochemical-metabolic, clinical risk factors and comorbidities associated with advanced fibrosis due metabolic dysfunction associated steatotic liver disease in patients with diabetes mellitus type 2. Material and methods: Case-control study. We reviewed 174 medical records of patients with metabolic dysfunction associated steatotic liver disease and type 2 diabetes mellitus treated at the Hospital Nacional Dos de Mayo from 2009 to 2018. The cases were patients with advanced fibrosis and controls without fibrosis. The presence of advanced fibrosis was defined by predictive clinical panels and/or liver biopsy result. To determine association, odds ratio, Pearson's chi-square and logistic regression analysis were calculated. Results: An association was found with age > 60 years, a body mass index ≥ 25 kg/m2, abdominal circumference in men ≥ 94 cm and abdominal circumference ≥ 88 cm in women, time of diabetes disease >10 years; chronic microvascular complications; HDL in women < 50 mg/dL, HDL in men < 40 mg/dL and albumin < 3.5 g/dL. About comorbidities were associations with chronic kidney disease and hypertension. After logistic regression analysis, age > 60 years, high body mass index, abdominal circumference in women, low HDL in women, chronic microvascular complications and hypertension remained independent risk factors. Conclusions: The risk factors for advanced fibrosis were age over 60 years, high body mass index, abdominal circumference ≥ 88 cm in women, chronic microvascular complications, low HDL level in women and hypertension as the main comorbidity.